Approach to the implementation of linear-assisted-based battery chargers - Martínez-García Herminio; García-Vílchez Encarna (E3S Web of Conferences, 2017)
This article shows the proposal of a linear-assisted regulator or linear-&-switching hybrid regulator with a constant switching frequency. The control loop of the system is based on the current-mode technique. The main disadvantage of a regulator with current-mode control is the inherent instability of the loop when switch duty ratios are greater than 0.5. In order to make stable the proposed linear-assisted regulator, the article shows the technique based on a slope compensation. This kind of voltage regulators is especially devoted to battery chargers in renewable energy systems.